The Christology of Origen - John C. Solheid (Religions)
In this essay, I will provide an overview of the Christology of Origen. Because Origen expressed his views in a variety of different literary and polemical contexts, and because the person of Christ pervades the entirety of his thought, I will focus my attention primarily on issues pertaining to his reception at Nicaea. I will highlight the key Origenian texts that shed light upon the theological questions with which he was preoccupied and address the role of the Monarchians in shaping his understanding of Christ. I will also address what I regard as one of Origen’s signature contributions to Christology, a contribution that has not yet received adequate attention, namely his understanding of the mystical body of Christ into which we enter at Baptism.